Teresa Diez me fecit and the Wall Paintings of the Convent of Santa Clara, Toro. Some Epigraphic Considerations - Arribas Ramos, Lara (Eikón / Imago, 2024)
The controversy surrounding the figure of Teresa Díez, based on the inscription with her name that was found on the wall paintings in the convent of the Poor Clares in Toro, proves the interest that medieval signatures have been generating in Art History. The relevance of Teresa’s epigraphic decision, however, goes beyond the study of this document as a source for the mere attestation of the lady’s role as author or commissioner of the pictorial cycles. Aspects such as the symbolic charge that the word has had since ancient times in its condition as a visual sign, or the location of the writing within a space of female enclosure permits an in‑depth study of some of the uses given to this inscription as an image. From this point of view, a review of it leads to the assertion, for this me fecit, of a function linked to the exercise of personal and institutional memory, through the enunciation of the lady’s name, the memory of her lineage and the intention of a timeless bond with the paintings.